Analisis Penerapan Lean Manufacturing untuk Menghilangkan Pemborosan di Lini Produksi PT Adi Satria Abadi - Khannan, Muhammad Shodiq Abdul; Haryono, Haryono (Jurnal Rekayasa Sistem Industri, 2015)
Productivity achievement at PT Adi Satria Abadi (Golf Gloves Division) is not optimal because ofthe waste. Value Stream Mapping as a Lean Manufacturing tool is used to map the production processand identify and eliminate the waste. The advantage of VSM is its capability to give visual map of valueadded flow process, necessary but non value added flow process, and non value added flow process. In thisstudy Waste Assessment Model (WAM) also have been implemented to identify the waste. The sequence ofthree greatest waste are Defect/Reject 24,73%, Unneccessary Inventory 18,80%, and Unneccessary Motion15,44%. This study can reduce production lead time 62,22 minutes and improve the production throughputby 77 pcs.